2001
DOI: 10.1291/hypres.24.209
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Sympathetic Responses to Dental Surgery with Local Anesthesia.

Abstract: We investigated changes in blood pressure and blood variables, including plasma catecholamines, serum glucose and insulin concentrations, during dental surgery. The study included 11 normotensive patients (age, 22.5+/-0.7 years) who underwent tooth extraction at Kyushu Dental College Hospital. Three to 7 days prior to dental surgery, blood pressure, pulse rate, and heart rate variability were measured every 30 min over 24 h. The low frequency (LF: 0.05 to 0.15 Hz) and high frequency (HF: 0.15 to 0.40 Hz) power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 15 publications
5
32
0
9
Order By: Relevance
“…Variations in glucose plasma levels during dental treatment have been the subject of study and controversy in the literature [26][27][28]. Tily and Thomas [26] compared the effect of adrenaline administration in the dental local anaesthetic solution on blood glucose concentrations in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in glucose plasma levels during dental treatment have been the subject of study and controversy in the literature [26][27][28]. Tily and Thomas [26] compared the effect of adrenaline administration in the dental local anaesthetic solution on blood glucose concentrations in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They observed no significant differences in pre-and post-operative blood glucose levels. Nakamura et al [27] investigated the changes in blood pressure, plasma catecholamines, glucose, and insulin concentrations in 11 normotensive patients during dental surgery and found that the administration of both local anaesthetics and tooth extraction activates sympathoadrenal outflow, resulting in increases of the systolic blood pressure, heart rate, plasma epinephrine, and serum glucose concentrations. They concluded that the adrenaline concentration increased and reached its peak just after the administration of local anaesthetics, yet the peak of adrenaline occurred within a time period similar to that of the increase of the serum glucose level, suggesting that there is a close relationship between the two variables.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of volatile and local anesthetics is known to increase blood glucose levels in animals and humans (Diltoer and Camu 1988;Nakamura et al 2001). Antipsychotic drugs, including phenothiazines, are also known to induce hyperglycemia irrespective of whether the drugs are typical or atypical (Haupt and Newcomer 2001).…”
Section: Inhibitory Effects Of Clinical Drugs On Glucose Transport Inmentioning
confidence: 99%
“…The released NE acts on α-receptors and blood pressure increases. Since plasma NE is mainly derived from sympathetic nerve endings, the concentration of NE could be used as an index of the baroreflex-mediated sympathetic nerve activity (1,2). For example, hypotensive responses caused by calcium antagonists in rats have been shown to correlate with the increases of plasma NE concentrations.…”
Section: Introductionmentioning
confidence: 99%